PENGARUH SIRKUIT BONGKAR PASANG TERHADAP FISIK MOTORIK ANAK KELOMPOK A DI RA TAUFIQIYAH KECAMATAN NGAJUM KABUPATEN MALANG - Mawidhotul Istiqomah; Mutiara Sari Dewi; Ari Kusuma Sulyandari (UNISMA, 2022)
Childern’s motor development is related to the ability to move the body in part. Disassembly circuit game is a circuit game that is easy to disassemble an install, has several game posts, each post has a different type of game. This study aims to determine the profile of physical motor development and the effect of the unloading circuit on the physical motor skills of group A children in RA Taufiqiyah Ngajum District. This research was conducted at RA Taufiqiyah with research subjects involving 16 students in group A. The method used in this study was a quasi-experimental design with one group pretest-posttest type of quantitative research. Data collection techniques were carried out by means of observation, tests, and documentation. The results showed that there was an effect of the unloading circuit on the physical motor skills of group A children in RA Taufiqiyah. This is evidenced by hypothesis testing, namely t-testand f-test. The results of the t test are known that the value of sig 0.00 < 0.05, the there is a significant effect of variable X on Variable Y. And the f test is known that the value of sig 0.00 < 0.05 0r 27.965 > 2.42, it can be concluded that there is a significant effect on variable X simultaneously on variable Y, then the result obtained are Ha is accepted and Ho is rejected. Unbalanced child development. Then use a circuit for stimulus for gross motor skill.